A Cross Sectional Study on the Prevalence of Abuse and Self Defence among Female Medical Students in Hubli (Indian Journal of Public Health Research & Development, 2021)
Background: Female abuse and harassment are burning issues of the present times and has shown increasingtrend of late.Harassment at workplace is a violation of Human Right.It degrades a person’s privacy anddignity leading to emotional stress,humiliation,anxiety and depression.Hence a study on the prevalence ofabuse among female medical students is highly warranted.Methods: A cross sectional study was conducted for a duration of one month among 100 female medicalstudents in Hubli,providing them with pretested semistructured questionnaire after obtaining informedoral consent.The participants were assured of their confidentiality.The data collected,was entered in excelsheet,tabulated and represented as tables and graphs.Conclusion: 95% female students felt that they have been harassed atleast once,among which 53% of theabusers were strangers.Verbal abuse was the most common form of abuse .Majority of them failed to informhigher authorities and had deep psycho social impact.Only a meagre of them were trained in self defensetechnics.
Keywords: Abuse, Self Defense, Female Medical Students, Hubli